Open Textbook Proof-of-Concept via Connexions - Judy Baker (Athabasca University Press, 2009)
To address the high cost of textbooks, Rice University’s Connexions and the Community College Open Textbook Project (CCOTP) collaborated to develop a proof-of-concept free and open textbook. The proof-of-concept served to document a workflow process that would support adoption of open textbooks. Open textbooks provide faculty and students with a low cost alternative to traditional publishers’ textbooks and can help to make higher education more affordable. Connexions provides a publishing platform for open textbook projects. The CCOTP acted as a liaison between community college faculty, open textbook authors, and Connexions. Challenges to the production and adoption of open textbooks include 1) faculty members’ and students’ expectations of high production quality and ancillaries for open textbooks, 2) methods for documenting and maintaining control over various versions, and 3) the process of converting existing open content to digital and accessible formats. Connexions holds promise as a means to overcome these challenges.